The Service Quality Effect of McDonald’s Self-Service Technology towards Customer Loyalty: A Cognition Affective Behavior Theory Approach - Muhammad Daffa Izzuddin; Zaenal Abidin (Journal of Advances in Information Systems and Technology, 2025)
Self-service technology (SST) is a technological interface that allows customers to obtain services independently. SST includes self-checkout machines, food or ticket ordering kiosks, internet services, automated gas stations, and others. The adoption of SST has been an endeavor for firms to improve service quality, enhance operational efficiency, and increase the likelihood of achieving competitive advantage gains. However, empirical evidence is needed to better understand customer expectations of SST service quality and how SST service quality impacts customer loyalty. Therefore, the purpose of this study is to examine SST service quality and its impact on customer satisfaction and customer loyalty. This study adopts the quantitative method and the self-service technology service quality (SSTQUAL) framework and cognition affective behavior theory. Data collection in this study was carried out by distributing questionnaires via google form with a purposive sampling technique, namely the target respondents were SST users at McDonald's aged 18 to 55 years. The results of the questionnaire collection obtained 285 data analyzed by partial least squares-structural equation model (PLS-SEM) with the help of SmartPLS 4 tools. Based on the results of the analysis conducted, 4 hypotheses were accepted. Self-service technology service quality variables are influenced by 5 quality dimensions such as functionality, enjoyment, assurance, design, and convenience. In addition, the self-service technology service quality variable has a positive influence on the customer satisfaction variable, which in turn positively affects customer loyalty. In other words, the service quality of self-service technology has a positive effect on customer loyalty through customer satisfaction.